DOSEN DAN PENGEMBANGAN BAHAN AJAR - R. Taufikurrahman (Research Institute and Community Engagement of IAIN MADURA, 2018)
A lecturer is a very important element in the education world. A lecturer is the heart of a university which not only determines the quality of the university but also the education and the graduations’ quality. If the lecturers have high quality, it will raise the quality of the university itself, and it happens vice versa. Although the university has a best design and program, if it is not supported by a high quality lecturer, it will end up far from the expectation, such as the university vision and mission.